2018
DOI: 10.23887/ijnse.v2i1.13907
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kuantitatif Kadar Nitrit dalam Produk Daging Olahan di Wilayah Denpasar Dengan Metode Griess Secara Spektrofotometri

Abstract: Nitrite is one of important food additive that used as a preservative and curing agent for the meat product. Since the adverse effect of nitrites to the human health has been reported, the government regulated maximum allowable nitrite content in meat product is 125 mg/kg. Hence, continuous monitoring of the existence of nitrite, especially in the meat products are important to conducted. Quantitative analysis of nitrite in the meat product, especially sausage has been described. The spectrophotometric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Source of animal origin food product Antibiotics residue (Jahantigh et al, 2020;Ngangguk et al, 2014;Pawestri et al, 2019;Wijaya & Pisestyani, 2011) beef, chicken Nitrate and nitrite (Alahakoon et al, 2015;Govari & Fexara, 2015;Habibah et al, 2018;Özbay & Şireli, 2021;Park et al, 2015;Yugatama et al, 2019) beef Scombrotoxin (Fatuni et al, 2014;Kung et al, 2016;Visciano et al, 2014) scombridae fish Pesticides (Anderson & Maede, 2014;Harwood & Dolezal, 2020;Rodríguez et al, 2016;Sanchez-Bayo & Goka, 2014) honey…”
Section: Chemical Hazard Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Source of animal origin food product Antibiotics residue (Jahantigh et al, 2020;Ngangguk et al, 2014;Pawestri et al, 2019;Wijaya & Pisestyani, 2011) beef, chicken Nitrate and nitrite (Alahakoon et al, 2015;Govari & Fexara, 2015;Habibah et al, 2018;Özbay & Şireli, 2021;Park et al, 2015;Yugatama et al, 2019) beef Scombrotoxin (Fatuni et al, 2014;Kung et al, 2016;Visciano et al, 2014) scombridae fish Pesticides (Anderson & Maede, 2014;Harwood & Dolezal, 2020;Rodríguez et al, 2016;Sanchez-Bayo & Goka, 2014) honey…”
Section: Chemical Hazard Potentialmentioning
confidence: 99%
“…Regulation of the Perpu MenKes RI (2012) regarding Food Additives has stipulated that the maximum threshold for the content of nitrites and nitrates as preservatives in processed meat products is 30 mg/kg and 50 mg/kg of ingredients, respectively. Several research results found that there are still processed meat foods on the market with nitrite content above the maximum threshold (Habibah et al, 2018;Yugatama et al, 2019). Now, some researchers are starting to try to develop natural preservatives to replace nitrite in processed meats such as with young radish, lettuce, cabbage, celery and red beets (Ko et al, 2016;Riel et al, 2017;Ferysiuk & Wójciak, 2020;Ozaki et al, 2020).…”
Section: Nitrate and Nitritementioning
confidence: 99%
“…(5) Berdasarkan penelitian sebelumnya yang dilakukan Habibah pada tahun 2018, menunjukkan bahwa dari 18 sampel sosis berbeda merek yang diperoleh dari berbagai toko di wilayah Denpasar terdapat 6 sampel sosis memiliki kandungan nitrit di atas ambang batas baku mutu Permenkes Nomor 1168 Tahun 1999. (6) Seiring dengan pembangunan Kota Makassar menuju kota dunia menyebabkan bergesernya pola hidup masyarakat menjadi lebih modern. Aktivitas masyarakat yang tinggi juga menuntut segala aspek kehidupan menjadi serba praktis.…”
Section: Pendahuluanunclassified
“…6 Dampak hematologi seperti methemoglobinemia yang mempengaruhi kemampuan untuk mengangkut oksigen sehingga menyebabkan warna kulit menjadi biru atau disebut sindrom blue-baby. 10 Lalu dampak pada neurologis seperti pusing, kehilangan kesadaran, hingga kejang sebagai akibat menurunnya kemampuan darah untuk membawa oksigen. 6 Oleh karena itu, air yang digunakan sebaiknya yang memenuhi persyaratan kualitas air bersih sesuai dengan Peraturan Menteri Kesehatan RI No.…”
Section: Pendahuluanunclassified